2007
DOI: 10.1080/09637480701288405
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of the commonly consumed composite dishes for the Barbados National Cancer Study

Abstract: A total of 152 weighed recipes were collected and we provide, for the first time, nutritional composition data for 32 commonly consumed food and drink items in Barbados. Such data are essential for assessing nutrient intake and determining associations between diet and prostate and breast cancer in the Barbados National Cancer Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Most of the dishes were fried in oil, resulting in a significant contribution of fat to the total energy. This is a finding similar to that found among fried foods in other cultures (Sharma et al ., ,b, ). A study on the nutritional composition of composite dishes from Barbados found a high fat content in many dishes, including pumpkin fritters, fried giblets, fried flying fish and sautéed corn beef (Sharma et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most of the dishes were fried in oil, resulting in a significant contribution of fat to the total energy. This is a finding similar to that found among fried foods in other cultures (Sharma et al ., ,b, ). A study on the nutritional composition of composite dishes from Barbados found a high fat content in many dishes, including pumpkin fritters, fried giblets, fried flying fish and sautéed corn beef (Sharma et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Only men ( n = 34) and women ( n = 45) who were the main food preparers and shoppers for their household were interviewed. Data were collected in June, 2011, and the methodology for the collection and analysis of composite dishes has been described in detail previously (Sharma et al ., ,b; Sharma, ). In brief, 24‐h recalls were collected from 79 community members and were conducted by locally trained field staff.…”
Section: Methodsmentioning
confidence: 99%
“…A blood sample was drawn to evaluate HbA1c and for future analyses of genetic variants; dietary intake was assessed with the administration of a validated food frequency questionnaire 8,9. Data relating to cancer staging and estrogen receptor status of cases were obtained by chart review at the Queen Elizabeth Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…To include information specific to Trinidadians, it was necessary to develop a new QFFQ as opposed to modifying those validated for Jamaica and Barbados where the populations are predominantly of African ancestry. In this regard, Sharma et al (2007aSharma et al ( , 2007b recognized the need to generate a culturally appropriate food list for the development of a QFFQ for use within the Barbadian population.…”
Section: Introductionmentioning
confidence: 99%